2019
DOI: 10.3390/nu11071641
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric-Adapted Liking Survey (PALS): A Diet and Activity Screener in Pediatric Care

Abstract: Clinical settings need rapid yet useful methods to screen for diet and activity behaviors for brief interventions and to guide obesity prevention efforts. In an urban pediatric emergency department, these behaviors were screened in children and parents with the 33-item Pediatric-Adapted Liking Survey (PALS) to assess the reliability and validity of a Healthy Behavior Index (HBI) generated from the PALS responses. The PALS was completed by 925 children (average age = 11 ± 4 years, 55% publicly insured, 37% over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 92 publications
1
17
0
Order By: Relevance
“…Criterion validity of the liking-based diet quality indexes in the present paper and others [53,60,61] is supported through ability to distinguish diet quality between patients with diagnosed depression versus controls as well as associations with the CRFS. We found lower diet quality across all of the diet quality indexes among those with depression, which agrees with previous literature (e.g., [62][63][64]).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Criterion validity of the liking-based diet quality indexes in the present paper and others [53,60,61] is supported through ability to distinguish diet quality between patients with diagnosed depression versus controls as well as associations with the CRFS. We found lower diet quality across all of the diet quality indexes among those with depression, which agrees with previous literature (e.g., [62][63][64]).…”
Section: Discussionsupporting
confidence: 65%
“…Utility of diet quality indexes also have been graded on their validity and reliability [59]. The liking-based diet quality indexes in the present study and others [53,60,61] have good variability, approaching normal distribution, construct validity, and internal reliability. Combining liking-based with frequency-based diet quality indexes can increase the precision in predicting diet-disease relationships [30,39] through indirect identification of dietary restraint (intake is less than level of liking) and of behavior change (intake is greater than level of liking).…”
Section: Discussionmentioning
confidence: 58%
“…PALS is a behavioral screener, construct/criterion measurement validated with 925 child–parent dyads in a paper/pencil format [ 29 ] and pilot validated with 525 child–parent dyads in an online format [ 35 ]. The online PALS assessed the participant’s level of liking/disliking of 1 practice (fun park) item that was always first in addition to 32 randomized items [ 29 , 30 , 35 ]: 3 each for fruits, vegetables, dairy, protein foods, high-fiber foods, salty foods, sweet foods, sugary drinks; 3 each for screen time and physical activities; 1 for brushing teeth; and 1 repeated (French fries) for internal test–retest reliability. Ratings were made on a continuous horizontal hedonic scale (7 faces labeled “love it,” “really like it,” “like it,” “it’s okay,” “dislike it,” “really dislike it,” “hate it”).…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral screeners must be easy to complete and understand, in order to facilitate participation, accurate reporting, and avoid parental resistance [ 27 ]. The pediatric-adapted liking survey (PALS), a simple proxy of behaviors that correlates with biomarkers of dietary intake and indirect measures of adiposity in children [ 28 , 29 ], is feasible for clinical settings, taking minutes to complete, with good test–retest reliability from clinical setting to home [ 30 ]. Although children and parents interfaced with and responded to the online PALS and messages, the focus of the present study was the child.…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring validity of dietary intake data is a prerequisite for any investigation into diet–disease associations. Three U.S. studies [10,16,17] and one Finnish study [18] focused on the validity of self-reported dietary intake data and derived dietary patterns. Validity refers to the extent to which a measurement actually measures what it is intended to measure.…”
mentioning
confidence: 99%